A re-evaluation of the Dynomenidae Ortmann, 1892 (Crustacea, Decapoda, Brachyura, Podotremata), with the recognition of four subfamilies - Guinot, Danièle (Zootaxa, 2008)
A re-evaluation of the Dynomenidae Ortmann, 1892, on the basis of morphological characters, allows four subfamilies to be recognised, viz. Acanthodromiinae n. subfam., Dynomeninae Ortmann, 1892, Metadynomeninae n. subfam., and Paradynomeninae n. subfam. Sequences of character states for each homologous character (morphocline) show a similar polarity. The Acanthodromiinae n. subfam. exhibits a plesiomorphic condition, both in body shape and fronto-orbital disposition as well as in the condition of the thoracic sternum, abdominal holding mechanism and gill structure. Both the Metadynomeninae n. subfam. and Dynomeninae are more advanced, the latter being more “carcinized” and the most derived. The Paradynomeninae n. subfam. evolved a specialised frontal and buccal region, by forming a projecting “face”. The family Dynomenidae, which presently comprises merely five extant genera and 21 species, but with a worldwide distribution, is amongst the most ancestral brachyuran families, with a good fossil record from the Late Jurassic onwards. A few fossil genera such as Kromtitis Müller, 1984, and Kierionopsis Davidson, 1966, appear to conform to the Paradynomeninae n. subfam. A key to the subfamilies of extant Dynomenidae is provided.